2019
DOI: 10.1108/f-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking life cycle cost drivers for sustainable office buildings in Denmark

Abstract: Purpose Sustainable building design suffers from a lack of reliable life cycle data. The purpose of this paper is to compare life cycle costs of sustainable building projects, examine the magnitude of various cost drivers and discuss the implications of an emerging shift in cost drivers. Design/methodology/approach This paper is based on data from 21 office buildings certified in Denmark according to the sustainable certification scheme DGNB. Findings The paper supports previous findings that construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…However, he claims that choosing energy-saving solutions will decrease the total costs for a single-family house in the future [21]. Findings from a Danish study where LCC data from 21 office buildings were compared show that construction costs amount to half of the total costs and the other half belongs to running costs [29]. In a Swedish case study [30], the construction phase dominated with 74% of total LCC, followed by operation and maintenance costs (18%) and design costs (8%).…”
Section: Lcc Outcome Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he claims that choosing energy-saving solutions will decrease the total costs for a single-family house in the future [21]. Findings from a Danish study where LCC data from 21 office buildings were compared show that construction costs amount to half of the total costs and the other half belongs to running costs [29]. In a Swedish case study [30], the construction phase dominated with 74% of total LCC, followed by operation and maintenance costs (18%) and design costs (8%).…”
Section: Lcc Outcome Distributionmentioning
confidence: 99%
“…Regarding the life cycle length of buildings, the review written by Emekci et al [9], includes publications with the LCC approach that classified the lifespan of buildings into three categories, <30 years, 30-50 years, and >50 years. Furthermore, Islam et al [5] concluded that the lifespan was in the range between 35 and 70 years, while several studies used 50 years as the median [5,[28][29][30]. For one office building located in the south of Sweden [30], the study includes the lifespan of 40 years.…”
Section: Life Cycle Length Of Buildingsmentioning
confidence: 99%
“…At this relatively early stage of the methodology, it is valuable to identify actions with low investment relative to the obtained savings rather than find the solutions with the least required investment over a defined period of time. Moreover, the majority of building owners are still not completely clear on the practical use and application of LCC calculations, and its uptake is still rather weak [45]. Regarding those considerations, in combination with the great difference in calculation methods for the CEP and NPV, it can be argued that the CEP provides satisfactory results for this stage of a renovation project, despite its simplified approach.…”
Section: Comparison Of Cep and Npv Of Single Actionsmentioning
confidence: 99%
“…Green leases are studied in two contributions: Rameezdeen et al (2019) have highlighted the role of facilities managers for environmental performance, while Ploeger et al (2019) have penetrated the legal issues that complicate the implementation of the concepts of a circular economy. Haugbølle and Raffnsøe (2019) have rethought how to deal with life cycle cost drivers for sustainable office buildings in Denmark.…”
Section: Articles In This Issuementioning
confidence: 99%